(untitled) (Research, Society and Development, 2022)
Covid-19 brought significant impacts in Brazil, causing deaths and leaving sequels in all states. Through the case, this study proposed to analyze the prevalence of cases and deaths by Covid-19 in the Brazilian territory. This is an ecological study, with a quantitative and observational approach. The research was developed through the Coronavirus Panel, a digital platform powered by the Federal Government. Data from the database were used, obtaining the number of cases and deaths in Brazil, Northeast and Ceará, in addition to the cities of Crato, Juazeiro do Norte and Barbalha. The incidence rate and the mortality rate were calculated for the mentioned locations. The number of hospitalizations due to ARDS was also collected. The results showed the Covid-19 mortality rate in the city of Barbalha to be higher than the mortality rate in Ceará and Brazil. Also, from epidemiological week 2 to week 10 of 2022, there was an increase in the absolute number of cases and deaths in the national territory. It was observed that SARS hospitalizations in the national territory affected more individuals aged 50 to 59 years. It is noteworthy that in Ceará there was the equivalent of 20.42% of hospitalizations for SARS found in the Northeast region. The present study is important in collecting data on cases and deaths, correlating them with social, territorial and biological aspects, making it necessary for new productions and investigations to be carried out on the subject.